Clinical Outcomes of Descemet Membrane Endothelial Keratoplasty in Eyes With Previous Radial Keratotomy. Issue 11 (November 2018) - Parker, Jack S.; Parker, John S.; Melles, Gerrit R. J.
Abstract : Purpose: To evaluate the clinical outcome of Descemet membrane endothelial keratoplasty (DMEK) performed in eyes with corneal endothelial decompensation and previous radial keratotomy (RK). Methods: Five consecutive eyes of 3 patients with previous RK underwent DMEK for endothelial decompensation; best spectacle-corrected visual acuity, maximum keratometry (Kmax), central corneal thickness, and intraoperative and postoperative complications were assessed. Results: By 6 months postoperative, all eyes had achieved a best spectacle-corrected visual acuity of ≥20/40 (≥0.5), 4/5 (80%) were ≥20/25 (≥0.8), and 2/5 (40%) were ≥20/20 (≥1.0). On average, central corneal thickness decreased by 122 μm, and Kmax decreased by 4.2 diopters. Successful rebubbling was performed on 1 eye at 3 weeks postoperatively; another eye experienced gaping of an old RK wound, that spontaneously resolved. Conclusions: DMEK is technically feasible in eyes with previous RK and may provide excellent outcomes. A significant change in the anterior corneal contour and associated refractive power of the eye may be anticipated depending on the amount of preoperative corneal edema and the number of RK incisions.